Digital learning : the key concepts - Rennie, Frank (Routledge, Taylor and Francis Group, 2020)
The new edition of Digital Learning: The Key Concepts is the perfect reference for anyone seeking to navigate the myriad of named concepts, approaches, issues and technologies associated with digital learning. Key terms are explained succinctly, making this book ideal to dip into for a quick answer, or to read from cover-to-cover, in order to gain a mastery of how digital concepts fit within the world of education. Fully updated to include important developments in digital practice and technology in education over the last ten years, this book takes the reader from A to Z through a range of relevant topics including: Course design Digital scholarship Learning design Open education Personal learning environments Social media and social networking. Ideal as an introductory guide, or as a reference book for ongoing referral, this quick-to-use and comprehensive guide is fully crossreferenced and complete with suggestions for further reading and exploration, making it an essential resource for anyone looking to extend their understanding of digital practices, techniques and pedagogic concepts.- Resumé vydavatel
Originally published: London ; New York : Routledge, 2006, under title E-learning / by Robin Mason and Frank Rennie.
Keywords: počítačem podporovaná výuka; internet; vzdělávání; World Wide Web; computer-aided learning; Internet; education; elektronické knihy; příručky; electronic books; handbooks and manuals